Journal of Soil and Water Conservation - Journal of Soil and Water Conservation (Taylor & Francis, 2026)
The Journal of Soil and Water Conservation (JSWC) is a multidisciplinary journal of natural resource conservation research, practice, policy, and perspectives. The journal has two sections: the A Section containing editorials and discussions, and the Research Section containing peer-reviewed research articles. Topics include, but are not limited to, erosion control, watershed management, forestry, agroecology, hydrology, soil science, wetland conservation, ecological restoration, water quality improvement, sustainable agriculture systems, and climate change adaptation and mitigation strategies.
FI 0.48
Q2
Keywords: Environmental Science; Ciencias de la tierra; Conservación; Acuerdos transformativos; Transformative agreements; Recursos naturales; Políticas; Erosión; Suelos; Humedales; Agua; Restauración ecológica